Integration of African traditional health practitioners and medicine into the health care management system in the province of Limpopo - Latif, Shamila Suliman (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MPA (Public Management and Planning))--University of Stellenbosch, 2010.